Purification and Serology of Banana Bunchy Top Virus - Estelitta S (Department of Plant Pathology, College of Horticulture, 1998)
Banana is one of the major fruit crop in Kerala and is often affected by the bunchytop disease caused by banana bunchytop virus. The disease is easily spread through infected suckers, which are used as the planting materials. Secondary spread is also seen through banana aphid, Pentalonia nigronervosa. Though field level quarantine measures may check the spread of the disease, rapid and convenient methods for the detection and identification of the virus in the suckers as well as in micropropagated plants have not been developed. In this background a study was designed and carried out to purify the BBTV, to produce antisera for developing a serological technique for the pre-symptomatic detection of virus in the planting materials of banana. Studies were also conducted to identify the type of nucleic acid of the virus and its morphology by direct electron microscopy. The study revealed that the disease incidence was maximum during August-November. The virus was not mechanically transmitted and tissue culture plants were the most susceptible planting materials for aphid transmission. Basic studies of virus-vector relationship were also conducted and the adult aphids were found to be effective vectors. In purification studies, among the different portions of banana plants used, the midribs of younger leaves yielded high concentration of the virus. Tissue culture plants yielded more virus concentration than other planting materials. Electron microscopy of the purified BBTV preparation revealed isometric particles of 18-22 nm size. Nucleic acids extracted from both healthy and infected samples were compared. The bands obtained were sensitive to DNase 1 and SI nuclease but not to RNase A, confirming the nucleic acid BBTV as ssDNA. SDS-PAGE analysis of BBTV coat protein revealed that it contained a major protein component of Mr 21000 with Rf value between that of β lactoglobulin (Mr 18400) and α chymotrypsinogen (Mr 25700). Antiserum of BBTV was produced in the rabbit and used for detection of virus specific antigens in different parts of the plant (midrib, petiole, leafsheath and rhizome) by chloroplast agglutination, agar gel diffusion, tube precipitation and ELISA. Among these methods ELISA was found to be highly sensitive for identification of the virus.